CovertSYS: A systematic covert communication approach for providing secure end-to-end conversation via social networks. (December 2022) - Taleby Ahvanooey, Milad; Zhu, Mark Xuefang; Mazurczyk, Wojciech; Li, Qianmu; Kilger, Max; Choo, Kim-Kwang Raymond; Conti, Mauro
Abstract: While encryption can prevent unauthorized access to a secret message, it does not provide undetectability of covert communications over the public network. Implementing a highly latent data exchange, especially with low eavesdropping/discovery probability, is challenging for practical scenarios, such as social and political movements in authoritarian regimes, military operations, and privacy preservation. Moreover, the current literature suffers from a low embedding capacity and monolingual applicability, limiting the amount of hiding secret data within short text messages using state-of-the-art algorithms, e.g., linguistic-based, structural-based, or coverless-based solutions. In this paper, we present a systematic covert communication technique called CovertSYS that enables a multilingual secure end-to-end conversation via messaging or social network platforms. The CovertSYS functions by encrypting a confidential message using a multi-factor authentication scheme and converting the encoded binary data into hidden Unicode symbols to be transmitted under cover of short text messages. We then conduct extensive experiments to confirm the security and validity of the proposed technique against state-of-the-art approaches. Our experimental results show that the CovertSYS provides a superior mean performance of 91.53% by improving the criteria scores: embedding capacity rate of 100%, imperceptibility rate of 76.4%, and distortion robustness rate of 98.2%. Finally, we discuss the practical implications of the proposed technique compared to the existing text steganography methods. Graphical abstract: Highlights: Various evaluation criteria based on literature and practical scenario have been discussed. Possible cyberattacks on covert communication systems have been described. The CovertSYS has been implemented in an Android prototype software. Experimental results show superior performance compared to existing related works.